Targeted metabolome and transcriptome analyses reveal changes in gibberellin and related cell wall-acting enzyme-encoding genes during stipe elongation in Flammulina filiformis - Li, Hui; Yao, Sen; Xia, Weiwei; Ma, Xinbin; Shi, Lei; Ju, Huimin; Li, Ziyan; Zhong, Yingli; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2023)
Flammulina filiformis, a typical agaric fungus, is a widely cultivated and consumed edible mushroom. Elongation of its stipe (as the main edible part) is closely related to its yield and commercial traits; however, the endogenous hormones during stipe elongation and their regulatory mechanisms are not well understood. Gibberellin (GA) plays an important role in the regulation of plant growth, but little has been reported in macro fungi. In this study, we first treated F. filiformis stipes in the young stage with PBZ (an inhibitor of GA) and found that PBZ significantly inhibited elongation of the stipe. Then, we performed GA-targeted metabolome and transcriptome analyses of the stipe at both the young and elongation stages. A total of 13 types of GAs were detected in F. filiformis; the contents of ten of them, namely, GA3, GA4, GA8, GA14, GA19, GA20, GA24, GA34, GA44, and GA53, were significantly decreased, and the contents of three (GA5, GA9, and GA29) were significantly increased during stipe elongation. Transcriptome analysis showed that the genes in the terpenoid backbone biosynthesis pathway showed varying expression patterns: HMGS, HMGR, GPS, and FPPS were significantly upregulated, while CPS/KS had no significant difference in transcript level during stipe elongation. In total, 37 P450 genes were annotated to be involved in GA biosynthesis; eight of them were upregulated, twelve were downregulated, and the rest were not differentially expressed. In addition, four types of differentially expressed genes involved in stipe elongation were identified, including six signal transduction genes, five cell cycle-controlling genes, twelve cell wall-related enzymes and six transcription factors. The results identified the types and content of GAs and the expression patterns of their synthesis pathways during elongation in F. filiformis and revealed the molecular mechanisms by which GAs may affect the synthesis of cell wall components and the cell cycle of the stipe through the downstream action of cell wall-related enzymes, transcription factors, signal transduction and cell cycle control, thus regulating stipe elongation. This study is helpful for understanding the roles of GAs in stipe development in mushrooms and lays the foundation for the rational regulation of stipe length in agaric mushrooms during production.